THE EFFECT OF VAGOTOMY ON THE MICROCIRCULATORY BED OF THE INTESTINE - Nuritdinov A.T. (Scholar Express Journals, 2022)
The paper presents an analysis of the results of experiments performed in animals (109 dogs - 4 series) with the aim of the effect of various types of vagotomyin on the hemomicrocirculatory bed and the lymphatic system of the small intestine in the next 3-7 days and 1-3-6 and 12 months after surgery. To assess the state of the lymphatic and blood vessels of the small intestine wall, the method of "biological" injection, interstitial injection of Gerota's blue mass and bichrome vascular infusion, as well as histological and histochemical research methods.It has been established that the development of morphological and functional changes in the blood vessels occurs simultaneously with various types of vagotomy, and the recovery period is significantly different. Morphofunctional changes are eliminated faster and more completely after selective proximal vagotomy (one month), and in animals that underwent stem and combined vagotomy, the period of elimination of congestion and morphological transformations of the vessel wall lasts up to three months. The revealed changes in the blood vessels and lymphatics of the small intestine after vagotomy can be taken into account when planning the management of the postoperative period, and especially for the purpose of correcting infusion therapy and choosing a diet.
Keywords: Vagus nerve; stomach; peripheral heart